Success Amidst Prejudice: Guanxi Networks in Chinese Businesses in Indonesia and Malaysia - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2000)
The study of ethnic Chinese business networks in Southeast Asia is under-theorized. In explaining their economic success, much of the literature on this phenomenon tends to adopt an excessively socio-cultural interpretation, focusing on guanxi. Such an essentialist reading tends to imbue cultural attributes with a sense of timelessness. However, one cannot ignore the ethnic prism through which political and economic life vis-à-vis the ethnic Chinese is viewed in Indonesia and Malaysia. To surmount the lack of trust in their operating environments, Chinese businesses resort to extensive use of embedded social-cultural and political networks. 'Political guanxi' highlights the need to consider the institutional and politico-economic aspects of Chinese economic success. Yet, the extensive use of political guanxi cannot guarantee long-term success, let alone the survival and prosperity of the citizen-Chinese community.